LINTANG : Media Edukatif Pembelajaran Literasi dan Numerasi Siswa Kelas Tinggi SDN 36 Cakranegara - Diah Ayu Rasmini; Ni Ketut Sandra Puspita Sari; Annisa Auliya Romdhani; Ida Ayu Sintiya Prayesti; I Putu Herry Widhi Andika (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2026)
The low level of literacy and numeracy skills among elementary school students requires innovative, interactive, and integrative learning media. This community service aims to describe the implementation of LINTANG (Literasi Numerasi Tangga Pintar) as a game-based educational medium for upper-grade students at SDN 36 Cakranegara, Mataram. The implementation method involved three main stages: preparation and situation analysis, media implementation using a collaborative Game-Based Learning approach, and an evaluation and reflection stage via direct observation and discussions with teachers. LINTANG adapts the snakes and ladders concept by combining reading comprehension challenges and numerical reasoning into a single game activity. The results indicated that utilizing this media successfully created an active, fun, and meaningful learning atmosphere. Students became more motivated and directly engaged in solving contextual problems. Thus, the LINTANG media serves as an effective alternative solution to strengthen the foundational literacy and numeracy competencies of elementary school students.